Close Reading as an Intervention for Struggling Middle School Readers. Issue 5 (February 2014) - Fisher, Douglas; Frey, Nancy
Abstract Thousands and thousands of middle school students around the world participate in reading intervention programs, many that are very expensive with limited effectiveness. We wanted to know if an after‐school intervention focused on close reading procedures could improve student achievement. Close reading of complex text involves annotations, repeated reading, text‐dependent questions, and discussions. This manuscript reports on 75 students in grades 7‐8 who received the close reading intervention and compares their outcomes with 247 students who received a traditional intervention. Results suggest that close reading can be an effective intervention, with significant increases in student attendance, self‐perception, and achievement.